Interview with Bernard Lavallé. A long vocation for History and teaching - Guibovich Pérez, Pedro M. (2025)
In this interview with Bernard Lavallé, we discuss his academic career and his scientific production. Lavallé recalls the beginnings of his teaching career and the friendly, professional relationships he formed.